The adaptation of South Sudanese Christian refugees in Ottawa, Canada: Social capital, segmented assimilation and religious organization - Lovink, Anton R (University of Ottawa (Canada), 2010)
This dissertation examines the adaptation of Christian refugees from Southern Sudan---primarily Dinkas and mostly educated---to living in Ottawa, Canada, not historically a gateway immigrant city. The discussion is based on sustained observation, documentation and analysis of South Sudanese refugees between 2005 and 2009, including 32 recorded interviews of adults, as well as a focus group held with young adults. It examines the findings through the lenses of social capital, with its focus on trust and reciprocity, and segmented assimilation to study the South Sudanese refugees' integration through their most important groupings: ethnic, gendered, racial and religious. The study also focuses on the cultural, gender and language dynamics of a nascent South Sudanese-focused congregation and a related East African congregation. The experiences of Anglican and Catholic congregations with Christian Sudanese refugees were also examined. The research suggests that inter-culturally competent ethnic and religious leadership is central to the ability of migrant groups in the Global North to have enough bonding social capital to mediate the adaptation process and to bridge or link to other groups. First-wave, mostly male, educated refugees often have the inter-cultural skills and agency to set up effective organizations, but a continued focus on their region of origin, facilitated by the Internet and cell phones, makes a sustained emphasis on organizational-supported living in Canada difficult. While the values of many Sudanese-born women and their children converge with those of mainstream Canadian society, men living within patriarchal value systems, supported by literal interpretations of Holy Scriptures, face challenges, and the resulting conflicts threaten family cohesion. Both the denominational and the ethnic churches, in supporting new migrants spiritually and socially, are caught between denominational parameters and goals of ethnic identity, culture and values maintenance, made more difficult by the Sudanese not having a common language. The dissertation also begins to analyze the impact for recent African Christian immigrants of a culture that emphasizes individual rights, including the effects of the increasing presence of openly gay leaders in the Canadian but not in the African Church.
Keywords: Religion, General.; Sociology, Ethnic and Racial Studies.